Married and Cohabiting Couples, 2010 (United States) ([Verlag nicht ermittelbar], 2011)
The Married and Cohabiting Couples, 2010 NCFMR Pilot Data is a nationally representative sample of U.S. married and cohabiting adults aged 18-64. Data are available for 1,504 married individuals representing 752 married couples and 646 cohabiting individuals representing 323 couples. Basic demographic characteristics are available related to age, income, educational attainment, gender, and race, and individual- and couple-level data. Knowledge Networks conducted a study on married and cohabiting couples' relationships with heterosexual couples 18-64 years of age. The data collection took place from July 26, 2010, to October 13, 2010. The main data collection was preceded by a small pretest to verify the data collection accuracy. The NCFMR Married and Cohabiting Couples pilot data offers rich data concerning relationship dynamics, both at the individual- and couple-levels including measures of relationship quality for both married and cohabiting individuals; measures of relationship stability, formation, and dissolution for married and cohabiting individuals; measures of role strain and conflict between work and family ties; measures concerning health decisions, power of attorney, and expected plan of care in later life; and detailed information on social support concerning each of these measures.